Functional and constraint logic programming : 26th International Workshop, WFLP 2018, Frankfurt/Main, Germany, September 6, 2018, Revised selected papers /: 26th International Workshop, WFLP 2018, Frankfurt/Main, Germany, September 6, 2018, Revised selected papers. (2019) - Unknown
No abstract available